Language Learning Motivation Among Malay Students Learning Mandarin As A Foreign Language - Tan , Teow Ghee (2010)
Much research has been done to identify language learners’ motivation for learning foreign languages in different contexts, but little information is available on Malay undergraduates’ motivation for studying Mandarin as a foreign language. The present study investigated language learning motivation among Malay students learning Mandarin as a foreign language in a public university in Malaysia. The study focused on the relationship between language learning motivation and other variables: course level, gender, metacognitive language learning strategies and achievement. A total of 860 students from three course levels participated in the study.